Printing assembly and structural regulation of graphene towards three-dimensional flexible micro-supercapacitors. Issue 31 (26th April 2017) - Li, Wenbo; Li, Yonghe; Su, Meng; An, Boxing; Liu, Jing; Su, Dan; Li, Lihong; Li, Fengyu; Song, Yanlin
Abstract : Precise patterning and controllable assembly of graphene into 3D architectures for flexible micro-supercapacitors was achieved by a printing assembly approach. Abstract : Flexible, high-performance miniature supercapacitors that offer reliable energy storage and output are desirable for use in portable and wearable electronics. Herein, we developed micro-supercapacitors with three-dimensional electrodes by printing assembly of graphene. By controlling the microstructures and macroscopic architectures of the graphene electrodes, superior electrochemical performance was achieved; especially, we demonstrated an advancement to address the limitation of areal capacitance. The unique three-dimensional graphene structure also provides this new class of micro-supercapacitors with exceptional mechanical flexibility. With these remarkable features, facile integration of the micro-supercapacitor array into flexible printed circuits was demonstrated. This printing assembly approach will pave the way to explore energy storage systems with diverse structures and extended functionalities.